From Manual to Digital Public Services: User Satisfaction through Digital Service Quality and Perception in a Local Fisheries Agency - Septi Kurniasih; Karmanis Karmanis; Charis Christiani (International Forum of Researchers and Lecturers, 2026)
This study examines how the transition from manual to digital services influences user satisfaction through digital service quality and user perception at the Marine and Fisheries Office of Pekalongan Regency. The research employs a mixed-methods approach, combining a quantitative survey (N = 40) using Pearson correlation analysis with qualitative interviews involving service leaders and operators. The results reveal very strong correlations between service quality, user perception, and user satisfaction, as well as the critical role of system stability and operator assistance in shaping user experience. Qualitative findings confirm that changes in work culture, leadership, and human resource adaptation are key factors in the success of digitalisation. The study implies that the success of digital public services is determined not only by technology but also by strengthening human resource capacity, simplifying service design, and providing operator support for users with low digital literacy. The limitations of this study include the small sample size, the single organisational context, and reliance on perception-based data. Future research is recommended to conduct comparative cross-agency studies, longitudinal approaches, and structural model testing to examine the mediating roles of digital literacy and operator assistance.